Evaluation and Dissemination of a Screening Tool to Improve the Identification of Trafficking Victims in the United States, 2012-2013 - Simich, Laura ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.Validation data (Human Trafficking Data, n = 180) was collected through 180 structured interviews with victim service provider clients who responded to the screening tool. The screening tool was administered by the victim service providers at regular intakes or subsequent interview sessions between July 2012 and June 2013. Service providers were instructed to invite any potential trafficking victims, that is persons who may have been trafficked or subject to similar crimes, whom they judge to be emotionally stable enough to participate. Status as a trafficking victim did not have to be determined in advance of the interview, since a mix of trafficked and non-trafficked clients in the study sample was necessary to establish the validity and predictive ability of the screening tool.Researchers also conducted confidential case file reviews during site visits at partner agencies, and in-depth interviews with service providers (n = 12 from 11 agencies), clients (n = 7 from 6 agencies) and key informant interviews (n = 12) with law enforcement officers, prosecutors and probation officers.